Multi-hop communication routing (MCR) protocol for heterogeneous wireless sensor networks. (1st January 2011) - Kumar, Dilip; Aseri, Trilok C.; Patel, R.B.
Effective energy management in heterogeneous wireless sensor networks (WSNs) is a more challenging issue compared to homogeneous WSNs. Much of the existing research has often assumed homogeneous sensor nodes in the networks. The energy preservation schemes for the homogeneous WSNs do not perform efficiently when applied to heterogeneous WSNs. In this paper, we have presented an energy-efficient multi-hop communication routing (MCR) protocol in order to address the traditional problem of load balancing, lifetime, stability and energy efficiency in the WSNs. MCR protocol is based on dividing the network into dynamic clusters. The cluster-heads election is based on weighted probability. The cluster's nodes communicate with an elected cluster head node by using single hop communication approach, and then the cluster heads communicate the information to the base station via multi-hop communication approach. Performance studies indicate that MCR effectively solves the problem of load balancing across the network, extends the network lifetime, stability and is more energy efficient in comparison to multi-hop low-energy adaptive clustering hierarchy (M-LEACH) and multilayer energy efficient cluster head communication protocol (MEECHCP).